Textual interactions in «Olive Branch Play» written by Azeddine DJILAOUI. - nouasria, ratiba; ouahab, khaled (El Omda in Linguistics and Discourse Analysis, 2025)
This article tackles the matter of absent textmanifestations in children’s theater, according to Azeddine DJILAOUI, who tried to raise a fundamental issue in the Arab theater, based on consistent and diverse system in thechildren’s theaterdistributed between religious and literary heritage. He has also tried to review the heritage through modern point of view, usingpositive interaction technics between heritage reference, children’s playwriting, while focusing on involving the child in theworld of symbolism, away from reductionist and complex vision and considering it as anexperimental step in addition to trying to turnchildren’s theater from traditional into renewal aspect